PROBLEMATIKA PERIZINAN KEGIATAN USAHA SARANG BURUNG WALET BERDASARKAN PERATURAN DAERAH NOMOR 15 TAHUN 2018 TENTANG IZIN PENGELOLAAN DAN PENGUSAHAAN SARANG BURUNG WALET PADA HABITAT BUATAN (STUDI DI KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU) - NIM. A1011191077, PUJI ASTUTI (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract The swallow's nest business activity is a form of business that takes advantage of the surrounding nature with the existence of swallows that fly freely and live wildly, so that cultivators only need to create an artificial habitat for breeding in the form of a building or buildings andother equipment to attract swallows to breed and build nests in this artificial habitat. .Currently, many swallow nest business activities have been developed in artificial habitats by people in Indonesia, including in North Putussibau District, Kapuas Hulu Regency.The formulation of the problem in this thesis is